Clear Lens Extraction with Foldable Intraocular Lens Implantation in a Case of Isolated Microspherophakia (Medical Journal of Shree Birendra Hospital, 2016)
Microspherophakia is an uncommon bilateral eye condition in which there is abnormal laxity of the lens zonules, leading to development of a spherical lens. Microspherophakia without systemic features is a rare presentation. The management of such a case is quite challenging. We report a case of isolated microspherephakia which was managed successfully with clear lens extraction with implantation of a foldable intraocular lens.